Finite Difference Analysis of Transient Heat Transfer in Surrounding Rock Mass of High Geothermal Roadway. (12th April 2016) - Zhang, Yuan; Wan, Zhijun; Gu, Bin; Zhang, Hongwei; Zhou, Peng
Abstract : Based on finite difference method, a mathematical model and a numerical model written by Fortran language were established in the paper. Then a series of experiments were conducted to figure out the evolution law of temperature field in high geothermal roadway. Research results indicate that temperature disturbance range increases gradually as the unsteady heat conduction goes on and it presents power function relationship with dimensionless time. Based on the case analysis, there is no distinct expansion of temperature disturbance range after four years of ventilation, when the temperature disturbance rangeR = 13.6 .